The spectrum of skin diseases seen in a Jamaican tertiary academic medical centerCapsule Summary - Althea D.C. East-Innis, MBBS, MRCP, DipDerm, MSE; Maxine M. Chung-Stanley, MBBS, DDSc; Alicia J.S. McNish, BMedSc, MBBS; Michael S.A. Fitz-Henley, MBBS, MSc, DM, DipDerm (Elsevier, 2021)
Background: The diversity of skin diseases seen in a dermatology clinic varies with the composition of the population. Objective: The aim was to document the spectrum of cutaneous disorders seen and the variation with sex, age, and seasons. Methods: This was a retrospective study on new patients attending an academic dermatology clinic in Jamaica during 2018. Disease frequencies and prevalence by sex, seasons, and age group were recorded. Results: There were 547 new patients with 329 females (60%) and 218 males (40%). The mean age was 36.8 years, ranging from 2 weeks old to 103 years old. The largest number of patients were in the third decade (20-29 years) (n = 139). More patients presented in the dry season and in spring and summer. The most common diagnoses were: seborrheic dermatitis (n = 65, 11.9%), acne (n = 56, 10.2%), and contact dermatitis (n = 38, 6.9%). The most common disease groups were dermatitis (n = 161, 29.4%), infections (n = 130, 23.8%), and inflammatory disorders (n = 129, 23.6%). Limitations: The generalizability of our findings may be limited, and selection bias may play a role in patients choosing to attend an academic dermatology clinic. Conclusions: Skin diseases varied with age, sex, and season with seborrheic dermatitis being most common.